Effect of postoperative proton pump inhibitor therapy on voice outcomes following phonomicrosurgery for vocal fold polyp: a randomized controlled study. (19th February 2016) - Lee, Y.C.; Na, S.Y.; Kim, H.J.; Yang, C.W.; Kim, S.I.; Byun, Y.S.; Jung, A.R.; Ryu, I.Y.; Eun, Y.G.
Abstract : Objective: To determine the effect of a postoperative proton pump inhibitor (PPI) on voice outcomes after phonomicrosurgery in patients with vocal fold polyp. Study Design: This is a prospective, randomized controlled study. Settings: This study was carried out in a tertiary care referral medical centre. Participants: A total of 48 patients underwent phonomicrosurgery for vocal fold polyps. After surgery, patients were randomized to the PPI group (lansoprazole 15 mg twice daily for 2 months) and the non‐PPI group. Main outcome measures: Voice handicap index (VHI) and perceptual and acoustic voice analysis were evaluated at baseline and 2 months after surgery. Results: Among 48 enrolled patients, a total of 42 patients [non‐PPI group ( n = 23), PPI group ( n = 19)] completed the study. The VHI, perceptual and most acoustic parameters significantly improved in both groups after surgery. However, there was no significant difference in the per cent of change in those parameters. Conclusion: Postoperative PPI treatment did not significantly influence voice outcomes after phonomicrosurgery in patients with vocal fold polyp.